The state of violence : terror in Latin America - Levy, Jim (Australian quarterly, 1986)
Violence is a time honoured means of effecting or of obstructing political change. Terror is the psychological component of such violence. In Latin America, it has not been guerrilla and other minority groups which have been responsible for the extremely high level of violence of the past several decades, but the state, particularly its military arm. The cases of Guatemala, El Salvador, Chile and Argentina bear out this contention